Application of liquid chromatography coupled to high-resolution mass spectrometry to measure urinary cortisol in loose housed sows - LEONTIDES, L.; DE CLERCQ, N.; SKAMPARDONIS, V.; LISGARA, M.; KONTOPIDIS, G.; KATSOULIS, K.; VANHAECKE, L.; MAES, D. (Journal of the Hellenic Veterinary Medical Society, 2018)
Cortisol is the most common physiological parameter used to measure welfare in pigs. In field studies evaluating stress in individual pigs which are group housed, the collection of spontaneously voided urine is practical. The purpose of the study was to apply a liquid chromatography coupled to high-resolution mass spectrometry approach to observe the patterns of diurnal urinary cortisol excretion among loose sows of three herds. We applied the analytical method in spontaneously voided urine of thirty, repeatedly sampled within a day, multiparous sows of three Greek herds. We found the level of urinary cortisol being highest before morning feeding [geometric mean of urinary cortisol to creatinine ratio being 2.72 (95% confidence interval: 1.17, 6.30), 5.65 (3.15, 10.14) and 2.60 (1.50, 4.50) in sows of herds A, B, and C, respectively] and lowest at 19:00 h [0.56 (0.27, 1.18), 1.24 (0.74, 2.07), 0.88 (0.55, 1.44)]. However, the patterns of diurnal urinary cortisol excretion appeared different among herds.